Potential CO2 reduction by implementing energy efficiency standard for room air conditioner in Malaysia - Mahlia, T.M. Indra; Masjuki, Haji Hassan; Choudhury, Imtiaz Ahmed; Saidur, Rahman (Elsevier, 2001)
This study attempts to predict the environmental impact of implementing an energy efficiency standard for room air conditioners in Malaysia. The ownership of room air conditioners has increased tremendously in this country. At present, there are about 528,792 room air conditioners in Malaysian households. In the year 2020, it will be about 1,511,276. The potential carbon dioxide reduction is based on the predicted electricity savings from implementing a minimum energy efficiency standard for room air conditioners. The electricity savings are calculated based on the predicted electricity consumption by a single air conditioner in the Malaysian household. The replacement of less efficient units of this appliance is reflected in reduced electricity consumption and emissions from power plants. The energy efficiency provisions of this regulation and agreement provide targets to save money, energy and, most importantly, to protect the environment.